ITEM ANALYSIS OF BUFFER SOLUTION MULTIPLE-CHOICE TEST - Kiky Setiawan; Rufi'i; Sabariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study evaluated the quality of an end-of-chapter multiple-choice test on buffer solution material by examining reliability, item difficulty, discrimination, and distractor effectiveness. A descriptive quantitative design based on classical test theory was used. The data consisted of responses from 35 students to 25 multiple-choice items and were analyzed using ANATES. The results showed a reliability coefficient of 0.72, indicating acceptable overall consistency. However, all items were categorized as very easy, with correct response rates ranging from 88.57% to 100%. Discrimination analysis showed that 17 items were poor, 5 were moderate, 2 were good, and 1 was very good. Distractor analysis also indicated that most incorrect options were non-functional because they were rarely or never selected. Only items 2, 7, and 23 were recommended for retention without revision, while most items required revision or removal. These findings indicate that total-score reliability alone is insufficient for judging assessment quality. Routine item analysis is therefore essential to strengthen the diagnostic usefulness of chemistry classroom assessment.